The Book and the Garden in the Poetry of N.Zabolotski of the 1930s - MKHITARYAN, KARINE (Bulletin of Yerevan University H: Russian Philology, 2021)
Images of the book and the garden, traditional for the world literature, get new meanings in Zabolotski’s poetry of the 1930s, differing from the ones in previous Russian poetry. The mentioned images reflect the characteristic features of the poet’s world view and his relation to the tragic pages of the Soviet reality in the 30s of the ХХ century.
Keywords: book, garden, insect, man, harmony, mentality, ethics, the Universe